Experimental BCI Prototype for Monitoring Brain Patterns in Drug Rehabilitation Patients - Espinoza Bazán, Fabián Andrés; Cabanilla Burgos, Cecilia Elizabeth; Palacios Ortiz, Francisco Gerardo; Sánchez Andrade, Dennisse Stephania; Catuto Cuenca, Gabriel Gerardo (Ecuadorian Science Journal, 2025)
This research aims to present an emerging solution based on BCI Technologies for patients in drug rehabilitation therapy. This work presents an introductory framework on the expansion of illicit markets and the increase in global drug consumption; thus, highlighting the need for innovative approaches, such as brain-computer interfaces (BCI), to improve rehabilitation and personalize addiction treatments. Subsequently, an EEG device is used to capture brain signals during addiction rehabilitation, processed with EEGLAB software. Finally, the researchers developed a BCI prototype for real-time monitoring of brain patterns in patients in addiction rehabilitation. Using the Emotiv Insight EEG device and EEGLAB software, brain signals are captured and processed to personalize therapies, improving the precision and effectiveness of the treatment. Initial results show the prototype's ability to detect variations in brain activity, optimizing therapeutic intervention and opening new possibilities in mental health.